Electrochemical Evaluation of Penta-Coordinated Fe Phthalocyanine During the Oxygen Reduction Reaction in Various Acidic Solutions - Tasca-Gottardo, F; Tasca-Gottardo, F; Zúñiga-Loyola, C; Zúñiga-Loyola, C (John Wiley and Sons Inc, 2024)
Iron phthalocyanine (FePc) was penta-coordinated with pyridine ligand (Py) grafted on carbon nanotube (CNT), to form (FePc-Py-CNT). The complex was studied as a catalyst for the oxygen reduction reaction ORR in seven different supporting electrolytes: OH− (0.1 M), OH− (1 M), NO3− (1 M), HSO4− (1 M), ClO4− (1 M), Br− (1 M), Cl− (1 M), to unveil anion-poisoning effects and mechanism. Through cyclic voltammetry and polarization curves in N2 and O2 saturated atmospheres, thermodynamic and kinetic data were acquired. In acid media, the formal potential Fe(III)/(II) (E0’Fe(III)/(II)) of the complex is biased to more negative potentials by the anion presence. Similar effects were observed for the onset potential (Eonset) during polarization curves for the ORR. When the ORR was performed in the presence of either ClO4−, or HSO4−, anions, Tafel analysis showed different values depending if were derived from the low or from the high overpotential regions, revealing an inner-sphere electron transfer mechanism (ISET). The Tafel values derived from measurements in the presence of Cl− and Br− anions do not change when extracted at low or at high overpotentials evidencing an outer-sphere reaction mechanism (OSET). Gibbs free energies were derived from poisoning tests confirming the ISET and OSET mechanisms. The poisoning effect is responsible for the immediate loss of performance for these catalysts during the ORR in acidic media. © 2024 The Authors. ChemElectroChem published by Wiley-VCH GmbH.